Vladimir Pavlovich Zagorodnjuk and Applied Arts in Belgrade between the Two World Wars - Prosen, Milan (Actual Problems of Theory and History of Art, 2022)
Vladimir Pavlovich Zagorodnjuk (Odessa, 1889 — Sydney, 1976) is one of many Russian artists who arrived in Yugoslavia in the early 1920s, in the first wave of emigration, and contributed to the visual culture of Belgrade in the period between the two world wars. This period is marked by the development in all areas of art and was so fruitful that even today, a century later, it has still not been fully researched and presented, demanding a deeper introspection of authorial contributions and stylistic trends, especially in the field of applied art. With the experience he gained while studying at the Ecole Nationale des Beaux Arts in Paris, he began his work in Belgrade in 1921 as a painter-scenographer of the National Theater. In the period 1923–1940, as an independent set designer for the National Theater, he staged 19 plays and 12 operas and about 20 plays in the period 1945–1950. Along with his scenographic work, in the period 1927–1939, he was noticed as a prolific sculptor, and created reliefs and facade sculptures of numerous public and private buildings in the capital and in other large centers of the kingdom. He cooperated with eminent architects of the period, often in favor of the Art Deco style, and contributed to its reception in Yugoslavia. He exhibited with the Society of Russian Artists (1928), with the group Krug (1929, 1930), at the Salon of Architecture (1931), at The first exhibition of theatrical painting (1938), as well as at the Salon of Russian Artists (1942 and 1943). He was awarded with Diploma de Medaille d’Or at The Exhibition of Industrial Decorative Modern Art 1925 in Paris, high State Decoration of Saint Sava in 1926 and The Medal for Labor Merits of III in 1949. In 1950, he immigrated to Australia, where he continued his artistic work to a lesser extent until his death in 1976 in Sydney. His three prolific decades of work in Belgrade left a considerable contribution, highly praised by contemporaries, but not entirely researched and evaluated by present historiography. Regarding previous researches, preserved edifices and documentation of the artist’s private legacy preserved in his family, as well as parts of his legacy donated to the Theater Museum of Serbia, this article tends to present the artistic oeuvre of V. P. Zagorodnjuk and to initiate its further consideration.